Determinants of Excellent Service Performance in Nurses: A Cross-Sectional Study - Rita Sariani Saragih; Martha Irene Kartasurya; Antono Surjoputro; Dwi Indah Iswanti (Universitas STRADA Indonesia, 2025)
Background: The low performance of nurses' services is a hotly discussed problem with several complaints from patients as health service users. Many factors affect the performance of excellent service both internally and externally. Purpose: to analyze the determinants of what factors support nurses in performing excellent service performance. Methods: quantitative design with cross-sectional approach. The sample size was 87 nurses from the entire population with D3 and NERS education, at least 6 months working in 6 surgical medical rooms with total sampling technique. The measurement instrument is a checklist and questionnaire consisting of statement items with 4 Likert scales. Validity and reliability tests on 30 respondents, the results r count> r table 0.361 with Cronbach alpha> 0.6. Descriptive, Pearson product-moment correlation and logistic regression were used to analyze the data with α=0.05. Results: The variables of perception of workload (p=0.004; Exp (B)=4.591), perception of leadership (p=0.012; Exp (B)=3.729), and motivation (p=0.018; Exp (B)=3.579) simultaneously affect the performance of excellent service by 33.5%. Conclusion: The determinant factor of nurses' excellent service performance is workload. Efforts are needed to increase work motivation, through suitability of salary/benefits received, positive policies from management, supervision, human relations, working conditions, and good organizational culture.